PENCEGAHAN KOMPLIKASI KEHAMILAN MELALUI EDUKASI TANDA BAHAYA KEHAMILAN DI KLINIK DAN RUMAH BERSALIN DELTA MUTIARA SUKODONO - Nurul Azizah; Rafhani Rosyidah (Universitas PGRI Adi Buana Surabaya, 2024)
Lack of knowledge and awareness about pregnancy danger signs is the cause of the high maternal mortality rate in Indonesia. This counseling aims to improve the knowledge and awareness of pregnant women and their husbands about pregnancy danger signs at the Delta Mutiara Sukodono Clinic and Maternity Home. Using an extension method involving lecturers and midwifery students from Muhammadiyah University of Sidoarjo, the activity included leaflet distribution, interactive lectures, discussions, and measurement of knowledge scores before and after the extension. The results showed a significant increase in knowledge scores from an average of 65 to 82. The discussion revealed the effectiveness of the counseling method in improving participants' understanding of pregnancy danger signs, which contributed to the prevention and early treatment of pregnancy complications. Conclusions emphasize the importance of effective health education in increasing public health awareness.